STRATEGIES FOR ENCHANCING THE SUSTAINABILITY OF BATIK BAKARAN AS CULTURAL HERITAGE AND TOURISM ASSET IN BAKARAN VILLAGE, PATI REGENCY - Agung Yuliyanto Nugroho; Aghfarina Ulayya Maghnani; Aditha Agung Prakoso; Moch Nur Syamsu (PT. Jurnal Center Indonesia Publisher, 2025)
Batik Bakaran is one of Indonesia’s traditional textile arts that holds significant cultural and historical value. Preserving this heritage is not only important for maintaining cultural identity but also for developing cultural-based tourism. This research aims to analyze the strategies implemented to sustain the existence of Batik Bakaran and promote it as a cultural tourism attraction in Bakaran Village, Pati Regency. Using a qualitative descriptive method, the study involved interviews with artisans, local government officials, and tourism stakeholders. The findings indicate that preservation efforts include the development of batik training programs, integration of batik education in schools, and the revitalization of traditional motifs. Meanwhile, promotion strategies focus on branding, digital marketing, and the creation of batik tourism packages. The study concludes that collaborative efforts between artisans, communities, and the government are crucial in ensuring the continuity and economic potential of Batik Bakaran through cultural tourism.